Echoes of Patriarchy: A Study of Gendered Language in George Eliot’s The Mill on the Floss - Jamshaid, Saima (Pakistan Languages and Humanities Review, 2025)
This paper aims to investigate Eliot’s The Mill on the Floss from the gender point of view. In the analysis of the two excerpts, the study assesses how the use of language reinforces and subverts the Victorian gendered power relations. Using Deficit Theory presented by Robin Lakoff, (1975) and Dominance Theory (Zamarman & West, 1975) this study delineates the subtle distinction between speech, gender, and power in The Mill on the Floss, providing a richer understanding of the Victorian society’s dynamics and its gender communication tradition. The results show that the male characters of this novel use command, explicitness, and dynamism, which are consistent with dominance theory because men use language to dominate. Their speech continues to portray the male dominance and rationality in the society. On the other hand, the female characters use positive and polite words and avoid direct communication, which supports the deficit model, asserting that women’s language is less formal and less effective than men’s. Their interactions also expose some instances of minimal resistance in defiance of the claim of weakness in a woman’s language. In this opposing approach, the study demonstrates how Eliot challenged gender roles present in the past, revealing strategies through which language erases inequality and social norms. The study would offer a more nuanced understanding of gendered interactions beyond binary power structures. Empirical data can support or refine existing qualitative interpretations, adding rigor to literary-linguistic studies.